A STUDY OF GRAMMATICAL EQUIVALENCE IN ABDULLAH YUSUF ALI’S ENGLISH TRANSLATION OF AL – QUR’AN - Achmad Farid (Diglossia: Jurnal Kajian Ilmiah Kebahasaan dan Kesusastraan, 2011)
Achmad Farid University of Pesantren Tinggi Darul ‘Ulum Jombang diglossiafbs@gmail.com   Abstract Grammatical is one of the language identities that determine the meaning. In the translation, the grammatical leads the most significant role because the translation mainly is not translating the words but translating the meaning into the other language. This study exposes the grammatical equivalence in Abdullah Yusuf Ali’s English translation of al – Qur’an. key words: equivalence, translation   Abstrak Tata bahasa merupakan salah satu identitas bahasa yang menentukan makna. Dalam penerjemahan, tata bahasa memerankan peranan yang sangat signifikan karena penerjemahan pada intinya bukanlah menerjemahkan kata – kata tetapi menerjemahkan makna ke dalam bahasa lain. Artikel ini memaparkan ekuivalensi ketatabahasaan dalam penerjemahan Al- Qur’an berbahasa inggris. kata kunci: ekuivalensi, penerjemahan